DEVELOPING FINITE ELEMENT COMPUTER PROGRAM FOR ELASTO-PLASTIC ROCK MODELING IN GEOMECHANICS ENGINEERING - K. WATTIMENA, RIDHO
Constitutive Law or Stress-Strain Relationship is one of the basic equations in finite element method. For soil/rock, this is non-linear and material models are required. One of them is strain hardening elasto-plastic material model [CHEN and BALADI (1985)] The objective of this research is to develop a fiinite element computer program for modeling the elasto-plastic material, and to give contribution in numerical modeling. Verification of the program using RHEO-STAUB of Rock Engineering Department, Federal Institute of Technology, Switzerland) indicates no significant differences of displacements and stresses. The verification using unconfined compressive strength test reveals no significant differences between calculated and measured displacements.